Collaborative Poetry Making: Words, Place, and Decolonisation. (4th May 2021) - Waldie, Angela; Yeo, Michelle
ABSTRACT: This article explores how poetry can contribute to the work of decolonisation for faculty development professionals and academic faculty more broadly. It explains how poetry has been significant for the authors in constructing and deconstructing our understandings of place. Through a discussion of literary theorists as well as Indigenous and non-Indigenous poets, it then considers how poetry might provide avenues for the personal and emotional work necessary for decolonisation. We share the process of a collaborative poetry workshop that we engaged in with participants at the 2019 Intercultural Intersections Conference at Thompson Rivers University, providing an overview of the practice and samples of the resulting poems. Through an analysis of these poems and the process itself, we consider the implications of this activity as a decolonising exercise.